THE STRUCTURE AND PROPERTIES OF MICROBIOCENOSIS IN DUMPS OF THE FUEL AND ENERGY COMPLEX OF UKRAINE - I. A. Blayda; T. V. Vasylieva; L. I. Sliusarenko; S. N. Shuliakova; V. F. Кhitrich (Biotechnologia Acta, 2018)
The work aimed to conduct complex chemical and microbiological study of the dumps of the fuel and energy complex of Ukraine. It is established that the qualitative composition of the aboriginal microbiota of the studied technogenic substrates does not to depended on the storage time, because it was determined by the chemical and mineralogical compositions and is mainly represented by the heterotrophic and acidophilic chemolithotrophic bacteria (AСB). It is noted that the number of all groups of microorganisms in dumps increased during long term storage due to internal processes and the impact of external climatic factors. In our experiment the ACB association demonstrated the maximum leaching activity when the divalent iron was as an energy source. It is also noted that the “silicate” bacteria present in the aboriginal consortium and have no leaching activity, significantly increase bioleaching rates by ACB. The results of the study indicate on the formation of resistant specific microbiocenoses in the dumps of the fuel and energy complex that can be used as sources of highly active strains obtaining for use in biotechnological processes of metal extraction.